2017
DOI: 10.1038/aps.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin I inhibits STAT3, but enhances STAT1 signaling in human cancer cells in vitro through disrupting actin filaments

Abstract: STAT1 and STAT3 are two important members of the STAT (signal transducers and activators of transcription) protein family and play opposing roles in regulating cancer cell growth. Suppressing STAT3 and/or enhancing STAT1 signaling are considered to be attractive anticancer strategies. Cucurbitacin I (CuI) isolated from the cucurbitacin family was reported to be an inhibitor of STAT3 signaling and a disruptor of actin cytoskeleton. In this study we investigated the function and mechanisms of CuI in regulating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 70 publications
(70 reference statements)
0
23
0
Order By: Relevance
“…Our results showed that cucurbitacin I had a positive correlation with STAT3 in the central nervous system, meaning that higher expression of STAT3 was correlated with worse response. However, cucurbitacin I had been proved as a potential inhibitor of STAT3 [81,82]. The converse might be explained by the tumor heterogeneity and the drug response was highly cancer-type-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that cucurbitacin I had a positive correlation with STAT3 in the central nervous system, meaning that higher expression of STAT3 was correlated with worse response. However, cucurbitacin I had been proved as a potential inhibitor of STAT3 [81,82]. The converse might be explained by the tumor heterogeneity and the drug response was highly cancer-type-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrantly active STAT3 promotes tumorigenesis, drug resistance, and metastasis in NSCLC . Downstream signaling effects of the STAT3 pathway can contribute to lung cancer and currently several STAT3 inhibitors show substantial anticancer and antiangiogenic effects . Finding novel agents with STAT3 suppressive activity is vitally important to improve NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were treated with B6, AZD1480, or DMSO for 30 min at 37 °C before incubation with biotinylated FLT3 (Cell Signaling Technology, Danvers, MA, USA) for 1 h at 37 °C. Samples were then processed following the protocol for the HTScan JAK2 Kinase Assay Kit [ 24 ].…”
Section: Methodsmentioning
confidence: 99%